Prediction of solid-state reactions for the formation of the chalcopyrites CuInS2, CuGaS2,CuAlS2 and CuAlSe2 starting from binary compounds - Hock, Rainer; et al. (physica status solidi (a), 2006)
In a recent work we have described the importance of epitaxy for the formation of CuInSe2 and CuGaSe2. In this article we identify epitaxial relations between binary selenide compounds serving as educts for the formation of the title compounds. From this we derive a set of possible chemical reaction equations for those solid-state reactions, which will preferably take place. By exploiting these reactions the chalcopyrite compounds can be synthesised smartly in short annealing processes at relatively low temperatures. (c) 2006 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.